UNIVERSITY STUDENTS RESPONSES’ TOWARDS THE USE OF PHET-BASED VIRTUAL LABORATORY ON THE BASIC OF SCIENCE CONCEPTS COURSE - Natsir, Siti Zahra Mulianti; Sahabuddin, Erma Suryani; Syamsuddin, Afdhal Fatawuri (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2025)
The rapid development of educational technology has brought significant changes to science learning, primarily by integrating virtual laboratories. These tools provide interactive and student-centered experiences that are more accessible than conventional labs. This study explores the importance of PhET-based virtual labs in enhancing students' understanding of energy and work concepts in a Basic Science Concepts course, emphasizing their relevance in modern, inquiry-based science education. This research analyzes university students’ perceptions of the usability and quality of PhET simulations used in the course. Using a quantitative survey method, data were collected from 161 randomly selected university students through a Likert-scale questionnaire. The results show an overall satisfaction rate of 71.68%, indicating a positive response categorized as "good." Students particularly appreciated the user-friendly interface and dynamic visualizations that encouraged independent exploration and more profound comprehension of abstract concepts. The study concludes that PhET-based virtual labs are practical supplementary tools in science education. Despite limitations such as reliance on self-reported data and short-term evaluation, the findings highlight the potential of virtual labs to enhance conceptual learning. Future research should investigate long-term learning outcomes and compare virtual, traditional, and blended learning environments to optimize instructional strategies.